Eagle Hotel, Monterey Street, San Luis Obispo, 1877 - Carleton E. Watkins::::::::: (1877)
Reproduction print. Looking southwest down Monterey Street toward San Luis Obispo de Tolosa Mission. The Eagle Hotel was the pioneer hotel of San Luis Obispo County. It later burned and was rebuilt as the Commercial Hotel.